A year in Thoreau's journal, 1851 - Thoreau, Henry David, 1817-1862.; Peck, H. Daniel (New York : Penguin Books, 1993)
Presents one full year of Thoreau's journal, written several years after his sojourn at Walden Pond, providing a record of his intellectual development and an example of his writings about the natural history of Concord.
Includes bibliographical references.
Adult
Keywords: Thoreau, Henry David, -- 1817-1862 -- Diaries; Thoreau, Henry David, -- 1817-1862 -- Diaries; Authors, American -- 19th century -- Diaries; American authors -- Diaries